SUGGESTIONS FOR IMPROVEMENTS TO SPORE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
P. Silvie, CIRAD Cotonou, Benin: 'I receive Spore which I always read with interest and pleasure, finding it a source of much useful information for our partners. Recently, I was talking about the bulletin with an official who wanted to take...